ANALYSIS OF STUDENTS MATHEMATICAL LITERACY ABILITY IN SOLVING PISA PROBLEMS IN TERMS OF STUDENT LEARNING INDEPENDENCE - Cici Ayu Chintya; Sehatta Saragih; Nahor Murani Hutapea (USN Kolaka, 2023)
Mathematical literacy skills are one of the essential aspects that students need to master because, through this ability, they can solve problems in everyday life. Providing Programme for International Student Assessment (PISA) questions is one of the teachers' efforts to develop students' mathematical literacy skills. This study aims to describe the observed mathematical literacy ability of students learning independence and analyze the difficulties experienced by students in solving PISA problems. The study subjects consisted of 20 students of SMPN 02 Siak Hulu. The research method used is descriptive. The research instrument is PISA test questions oriented to quantity content, learning independence questionnaires, and interviewguidelines. The data obtained is analyzed by reducing, presenting, and drawing conclusions. The result of this study is that students doing PISA questions are still experiencing difficulties. This difficulty occurs because students are unfamiliar with PISA model questions. They do not understand the meaning of the problem, do not understand the material in the problem, are confused about determining mathematical concepts, and cannot apply problem-solving strategies.